A monolithic compliant large-range gravity balancer. (August 2016) - Radaelli, G.; Herder, J.L.
Abstract: A new monolithic fully compliant gravity balancer is designed with help of a design approach based on shape optimization. The balancer consists of one single clamped–clamped complex-shaped beam on which a weight is attached. The beam is modeled as a planar isogeometric Bernoulli beam. The goal function of the optimization consists of an energy based evaluation of the load path of the beam which is compared with a desired response. The best result of the shape optimization has been constructed out of polycarbonate sheet and out of glass-fiber reinforced plastic laminate. Both have been tested on a compression test bench. The theoretical model has good resemblance with the experimental results.